Pengaruh Pengeluaran Pemerintah, Foreign Direct Invesment dan Emisi Karbon Terhadap Pertumbuhan Ekonomi Negara Anggota OKI - Adelina Hasibuan; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study analyzes the effects of government expenditure, foreign direct investment (FDI), and carbon emissions on economic growth in 18 low- and middle-income member countries of the Organization of Islamic Cooperation (OIC) during the period 2016–2023. The data used consist of panel data obtained from the World Development Indicators and other relevant international sources. The analysis employs the Fixed Effects Model (FEM), selected based on the results of the Chow test, Hausman test, and Lagrange Multiplier test. The findings indicate that government expenditure has a negative and statistically significant impact on economic growth, suggesting inefficiencies in budget allocation and management. FDI shows a positive but statistically insignificant effect, implying that it has not made a substantial contribution to economic growth. Meanwhile, carbon emissions have a positive and statistically significant effect, indicating that economic growth still relies on carbon-intensive activities. Overall, the study highlights the need for integrated policies to improve fiscal efficiency, optimize the role of foreign investment, and promote a transition toward more sustainable energy in order to support long-term economic growth.